2011
DOI: 10.1007/s11920-011-0214-2
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Adolescent Substance Abuse Treatment

Abstract: Alcohol and other drug use among adolescents has been a public health problem for decades. Although some substance use may be developmentally routine, a concerning number of adolescents meet criteria for a substance use disorder and could greatly benefit from a quality treatment experience. However, parents and health care providers want evidence of the efficacy of adolescent-specific treatment programs. This review summarizes four factors surrounding the efficacy of current adolescent treatment programs: 1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 22 publications
2
80
0
3
Order By: Relevance
“…112 A 2013 metaanalysis concluded that approaches targeted to families and group-based interventions had the greatest influence on response to treatment (greater effect size), 113 but the therapeutic approaches used in different studies assessed are not clear. Brief interventions, such as motivational interviewing for adolescents, have a small but significant effect size, which remains over time and has the greatest impact on reducing the use of illicit substances.…”
Section: Non-pharmacological Approachesmentioning
confidence: 99%
“…112 A 2013 metaanalysis concluded that approaches targeted to families and group-based interventions had the greatest influence on response to treatment (greater effect size), 113 but the therapeutic approaches used in different studies assessed are not clear. Brief interventions, such as motivational interviewing for adolescents, have a small but significant effect size, which remains over time and has the greatest impact on reducing the use of illicit substances.…”
Section: Non-pharmacological Approachesmentioning
confidence: 99%
“…mon types of psychosocial treatments for adolescents have been identified as: (i) family-based therapy; (ii) individual and group therapy -these mainly include CBT, brief interventions and motivational approaches, and contingency management reinforcement approaches; (iii) 12-step programmes; and (iv) therapeutic communities. [14] Different types of pharmacological therapies may be used for treating and managing AUDs. According to Clark, [15] these are most effective in conjunction with psychotherapy and are used for addressing withdrawal, reducing craving, minimising alcohol's reinforcing proper ties, and/or addressing other mental health conditions.…”
Section: Box 2 Items Of the Crafftmentioning
confidence: 99%
“…In addition, the references of included studies and a number of relevant reviews were screened (i.e., Cavaiola, Schiff, & Kane- Cavaiola, 1990;Deas & Thomas, 2001;Elliott, Orr, Watson, & Jackson, 2005;Passetti, Godley, & Godley, 2012;Passetti & White, 2007;Williams & Chang, 2000;Winters, Botzet, & Fahnhorst, 2011). A list with studies on Narcotics Anonymous found on the Internet was also screened (White, Budnick, & Pickard, 2011).…”
Section: Search Strategymentioning
confidence: 99%
“…There is a wide range of treatments for substance misuse available, including brief interventions, cognitivebehavioral therapy, motivational enhancement therapy, and family-based therapy (Stoffel & Moyers, 2004;Winters, Botzet, & Fahnhorst, 2011). A special kind of substance use treatment is self-help, which was defined by Humphreys and colleagues (2004, pp.…”
Section: Introductionmentioning
confidence: 99%